Competition, Reputation and Cheating - Paolo Vanin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
Under repeated market interaction, reputation and competition may drive out of the market those firms that do not comply with their quality promises. One may thus presume that competitive pressure improves average market quality. This paper shows that the opposite may be true in an endogenous entry, repeated interaction, linear demand oligopoly model, in which introductory prices may be used as quality signals. Cheating firms may enter the market, fool even rational consumers, and exit the market when discovered, implying a failure of the basic reputation mechanism and an increasing time path of prices. Markets for closer substitutes tend to have a lower initial average quality and less trusting consumers, whereas the number of competitors has no clear relationship with average quality.
Keywords: L13; L14; L15; 330